2015
DOI: 10.1080/13658816.2015.1018266
|View full text |Cite|
|
Sign up to set email alerts
|

Usability of VGI for validation of land cover maps

Abstract: Volunteered Geographic Information (VGI) represents a growing source of potentially valuable data for many applications, including land cover map validation. It is still an emerging field and many different approaches can be used to take value from VGI, but also many pros and cons are related to its use. Therefore, since it is timely to get an overview of the subject, the aim of this article is to review the use of VGI as reference data for land cover map validation. The main platforms and types of VGI that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 62 publications
0
65
0
Order By: Relevance
“…A diverse range of approaches exist for quality assessment and control, e.g., [69][70][71], and guidelines for some applications are emerging [72].…”
Section: Quality and Use Of The Data For Researchmentioning
confidence: 99%
“…A diverse range of approaches exist for quality assessment and control, e.g., [69][70][71], and guidelines for some applications are emerging [72].…”
Section: Quality and Use Of The Data For Researchmentioning
confidence: 99%
“…Many methods have then been proposed to assess VGI quality; a review can be found in [4][5][6], among others. The quality assessment of VGI POIs is essential as many applications are based on such data, and can be affected by low-quality POIs.…”
Section: Introductionmentioning
confidence: 99%
“…Capitalizing on volunteered geographic information is also an active way of collecting large amounts of reference datasets that are based on volunteers using high-resolution satellite images, geo-tagged photographs and OpenStreetMap [29][30][31]. Data will also become available in the near future from the new EU-funded LandSense citizen observatory.…”
Section: Benefitting From Other Data Sourcesmentioning
confidence: 99%
“…More recently, the Geo-Wiki platform has been extended to LACO-Wiki, which is an online land cover and land use validation platform and aims at creating a community around the sharing of reference datasets globally [28]. The possibilities of using other VGI (Volunteered Geographic Information) data sources such as geo-tagged photographs and OpenStreetMap are also being tested for map validation purposes [29][30][31].…”
Section: Independent Map Validation Has Become Commonplacementioning
confidence: 99%